Internal history and external history? - Armocida, Giuseppe (Medicina Historica, 2018)
Many years have passed since Luigi Belloni had opened a discussion on two different paths of Italian medical history, distinguishing an external history of medicine and an internal or technical history of medicine - e dobbiamo intendere che il dibattito su certe questioni torna spesso a riemergere nei nostri ambienti. [...]